Dijital Evrende Mimesisi Yeniden Düşünmek; Avatar Filmi - İğneci Süzen, Rana (The Turkish Online Journal of Design Art and Communication, 2012)
Cinema, with its unique way of expression, states a wide range area of capabilities. This is a “narrative” form that conveys a strong sense and discourse which includes its own unique codes and techniques. Even if this narrative form houses infinite contingencies, basically, it is based on showing and performing. While the Modernist or the Avant-garde cinemas, which are experiencing the modern narrative techniques, are on the other side of these narrational contingencies, the Classical Cinema has always managed to protect its ties with the mimesis concept which exists since Aristotle thanks to its practices on generally used forms of dramatic narration which are showing and performing. Mimesis, accordingly, states the form in which the narrator is excluded and in which the events are re-fictioned and relived in a present time. Here, the context of making the events ‘lived’ without a mediator, establishes a virtual reality which is over the feelings of “katharsis” and “identification” with the application of digital 3D effects in the cinema of today. This study argues how the “mimesis” concept is evolutionized by the digital capabilities of the cinema or what this new form has added to the narrative capabilities of the cinema. Accordingly, the 3D movie Avatar directed by James Cameron will be analysed in accordance in the cinematic narrative forms.
Keywords: Mimesis; 3D Cinema; Classic Cinema; Cinematic Narration; Katharsis; Benzetme; 3D Sinema; Klasik Sinema; Sinematik Anlatım